Advances on refractory castables drying process coupling experimentation and computational modelling - Moreira, Murilo Henrique (Universidade Federal de São Carlos, 2025)
The water withdrawal from hydraulically bonded refractory castables is of fundamental importance to ensure their performance, as cracks, damage, and ultimately explosions may occur if this step of the installation is not properly conducted. Currently, there is a lack of a scientific approach that includes both experimental and innovative computational studies for the evaluation of drying. This absence makes the improvement of this stage unfeasible, leading to long and costly processes, both financially and environmentally, which limits a broader adoption of these materials. Thus, this thesis aims to advance the understanding of the drying process, based on the combination of experiments and numerical models. The main aspects are divided into three groups: i) the analysis of water removal via neutron and X-ray tomography, ii) the development of a phase-field model for the thermohygromechanical simulation of the drying process and iii) the investigation of the effect of volume on this phenomenon. The in-situ visualization of the process unequivocally confirmed the moisture clogging hypothesis (for the first time detected for refractory materials), and its application in samples containing different polymeric fibers (polyethylene, polypropylene and cellulose) revealed the complex dynamic and non-linear behavior induced by such additives. The phase-field model was correctly implemented, in agreement with results in the literature, and its potential was evidenced by comparing different heating methods that can be adopted by the industry. Finally, a volume effect was found experimentally, related to thermal, mass and mechanical aspects, which strongly impact the probability of explosion, and the existence of phenomena such as vapor recondensation and its sudden evaporation. The technical advances resulting from this project brings a deeper understanding of the complex factors that dictate the optimization of the drying process and even the behavior of Portland cement-based structures under heating, thus providing sound advances in sectors crucial to society.
Avanços no processo de secagem de concretos refratários: acoplamento entre experimentação e modelagem computacional
Keywords: Refractories; Castable; Drying; Simulation; Concretos Refratários; Refratários; Concretos; Secagem; Tomografia; Simulação; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS